2022
DOI: 10.3389/fonc.2022.817222
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Non-Participation in Population-Based Breast Cancer Screening: A Systematic Review and Meta-Analysis

Abstract: BackgroundBreast cancer (BC) screening can be performed in a screening program (BCSP) or in opportunistic screening. The existing reviews on the determinants of non-participation depend on self-reported data which may be biased. Furthermore, no distinction was made between the probably different determinants of both screening strategies.ObjectiveTo find the determinants of non-participation in BCSP by means of a meta-analysis.MethodsPubMed, Embase, and Web of Science were searched for observational studies whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…Accessibility has several dimensions including acceptability. The list of potential barriers includes, in addition to health literacy, sociodemographic, cultural, psychological, and migration related factors, travel distance, and healthcare system barriers 226414445. The results of this study indicate that efforts other than translated information are needed to increase attendance.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Accessibility has several dimensions including acceptability. The list of potential barriers includes, in addition to health literacy, sociodemographic, cultural, psychological, and migration related factors, travel distance, and healthcare system barriers 226414445. The results of this study indicate that efforts other than translated information are needed to increase attendance.…”
Section: Discussionmentioning
confidence: 90%
“…On the basis of the results of this trial, no reason exists to expect that translated information alone will increase attendance at BreastScreen Norway for immigrant women in the future. Several aspects of the screening programme should be considered to facilitate a higher attendance among immigrant women, such as guaranteed access to female radiographers and the use of an interpreter service 41. A guarantee of a female radiographer is difficult to give in Norway, and the interpreter service is challenging in a screening setting.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, using individual‐level data from the EHIS 2013 to 2015, Bozhar et al found that besides educational attainment, women aged 50 to 54, born in a non‐EU country, widowed or never married, and with lower household income were less likely to report having had a mammography in the past 2 years 20 . Disparities in use of screening by socioeconomic status have also been consistently found in the context of organised programmes 21 . Therefore, large improvements could be potentially achieved by better reaching women in the most deprived stratum of the population.…”
Section: Discussionmentioning
confidence: 94%
“…20 Disparities in use of screening by socioeconomic status have also been consistently found in the context of organised programmes. 21 Therefore, large improvements could be potentially achieved by better reaching women in the most deprived stratum of the population.…”
Section: Self-reported Use Of Mammography In European Countries By Hd...mentioning
confidence: 99%
“…Previous studies showed that socio-economic factors, such as by low income, low education, being unmarried, and being an immigrant are associated with non-participation in both breast and cervical cancer screening (Ding et al , 2022) (Jolidon et al , 2020).…”
Section: Discussionmentioning
confidence: 99%